A Study of the Effects of Alum and PAC on the Coagulation Process of Dug Well Water - Finar Ramadhan; Lalak Tarbiyatun Nasyin Maleiva; Putranty Widha Nugraheni (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
The local population of Pal IX Village in West Kalimantan heavily depends on dug wells as their main source of obtaining clean water. The prolonged consumption of elevated concentrations of manganese (Mn) and iron (Fe) in water sourced from dug wells has neurotoxic effects on both adults and children. Therefore, it is imperative to employ alum and PAC coagulants for the treatment of dug well water in order to comply with the established national quality standard. However, the utilization of both coagulants resulted in an elevation in the levels of iron (Fe), hence restricting the capacity to satisfy the quality standards. An augmentation in the mass of the coagulant is associated with a decline in the reduction efficiency. It is indicated that utilizing a mass of 0.5 grams of alum coagulant is the most favorable choice, resulting in a reduction of 50.14% for total dissolved solids (TDS), 86.25% for color, 97.70% for turbidity, and 94.48% for the concentration of Mn metal. By PAC coagulant, it has been determined that an ideal coagulant mass of 0.5 gram produces favorable outcomes with a TDS reduction of 45.08%, a color reduction of 97.71%, a turbidity reduction of 97.22%, and a Mn reduction of 95.04%.Â Keywords: Alum; PAC; coagulant; coagulation; dug well water